硫酸あるいは硝酸溶液添加時のCaあるいはMgの水酸化物から調製したCaあるいはMg含有水溶液の緩衝作用 - 安池, 俊也; 笹野, 順司; 世山, 奨大; 横山, 誠二 (鉄と鋼, 2020)
It has been suggested that the eluate from steelmaking slag has a buffering effect. However the mechanism of the buffering action has not been elucidated. The slag eluate contains various elements such as Ca, Mg, Si, Al, and so on. CO2 in air influence pH. Therefore, in this study, we performed a model experiment in which an aqueous solution of sulfuric acid or nitric acid, which is a representative acid of the acid rain, was added to an aqueous solution containing Ca or Mg in Ar. Its solution was prepared from its hydroxide and ultrapure water. The pH behavior of the solution was investigated to clarify the factors which determined the pH. When the acid solution was added to the solution containing Ca or Mg, pH decreased gradually. At a certain amount of addition of the acid solution, the pH decreased steeply, and, subsequently, decreased gradually. The pH of the solution containing Ca or Mg was determined by the charge balance of ions in the solution. Those two gradual decreases in pH corresponded buffering action. This was caused by the reaction of water dissociation. The equivalence point was the point where concentration of Ca2+ or Mg2+ was equal to the concentration of SO42–, or twice that of NO3–. The pH at this point was seven. The sharp pH change occurred at pH of approximately seven.